TATA KELOLA KOLABORATIF DALAM PENGEMBANGAN EKOWISATA SUNGAI MUDAL DI KABUPATEN KULON PROGO - Ningrum, Paulita Sekar; Nugroho, Hanantyo Sri (PRAJA: Jurnal Ilmiah Pemerintahan, 2025)
This research examines collaborative governance in the development of Mudal River Ecotourism. The location of this research is Banyunganti, Jatimulyo Village, Girimulyo, Kulon Progo. The subjects of this research are the owners and managers of Kudal River Ecotourism. In this research using observation method with qualitative approach. The theory used in this research is Ansell and Gash's theory related to collaborative governance. The results showed that Mudal River Ecotourism received funding assistance from PT PLN from 2016 to 2023, for the development of infrastructure, facilities and infrastructure, this was deliberately done because this was one of the CSR programs from PT PLN as a form of community empowerment. Although funding was stopped in 2023, until now the communication between PT PLN and Mudal River Ecotourism remains well established.